Soil fauna responses to invasive alien plants are determined by trophic groups and habitat structure: a global meta‐analysis - Abgrall, Corentin; Forey, Estelle; Chauvat, Matthieu (Oikos, 2019)
Despite increasing frequency of invasions by alien plant species with widespread ecological and economic consequences, it remains unclear how belowground compartments of ecosystems are impacted. In order to synthetize current knowledge and provide future directions for research we performed a meta‐analysis assessing the impact of invasive alien plant species on soil fauna abundance. Compared to previous synthesis on this topic, we included together in our model the trophic group of each soil faunal taxa (from herbivores to predators) and habitat structure, namely open and closed habitats (i.e. grass and shrub dominated areas versus forested areas). In doing so, we highlighted that both moderators strongly interact to determine the response of soil fauna to the presence of invasive alien plants. Soil fauna abundance increase in the presence of invasive species only in closed habitats (+18.2%). This pattern of habitat‐dependent response (positive effect in closed habitats) was only found for primary consumers (i.e. herbivores +29.1% and detritivores +66.7%) within both detritus‐based and live root‐based trophic pathways. Abundances of predators and microbivores did not respond to the presence of IAS irrespective of habitat structure. For several groups, the habitat structure (open or closed) significantly drove their responses to the presence of invasive alien species. In addition, we carefully considered potential sources of bias (e.g. geographic, taxonomic and functional) within the collected data in an attempt to highlight gaps in available knowledge on the subject. Our findings support the conclusions of previous studies on the subject by demonstrating 1) that soil fauna abundance is impacted by biological invasions, 2) that initial habitat structure has a strong influence on the outcome and 3) that responses within the soil fauna differ between trophic levels with a stronger response of primary consumers.